An emerging class of new therapeutics targeting TGF, Activin, and BMP ligands in pulmonary arterial hypertension. Issue 3 (27th April 2022) - Upton, Paul D.; Dunmore, Benjamin J.; Li, Wei; Morrell, Nicholas W.
Abstract: Pulmonary arterial hypertension (PAH) is an often fatal condition, the primary pathology of which involves loss of pulmonary vascular perfusion due to progressive aberrant vessel remodeling. The reduced capacity of the pulmonary circulation places increasing strain on the right ventricle of the heart, leading to death by heart failure. Currently, licensed therapies are primarily vasodilators, which have increased the median post‐diagnosis life expectancy from 2.8 to 7 years. Although this represents a substantial improvement, the search continues for transformative therapeutics that reverse established disease. The genetics of human PAH heavily implicates reduced endothelial bone morphogenetic protein (BMP) signaling as a causal role for the disease pathobiology. Recent approaches have focused on directly enhancing BMP signaling or removing the inhibitory influence of pathways that repress BMP signaling. In this critical commentary, we review the evidence underpinning the development of two approaches: BMP‐based agonists and inhibition of activin/GDF signaling. We also address the key considerations and questions that remain regarding these approaches. Key Findings: Dysregulated bone morphogenetic protein (BMP) and activin signaling are associated with the pathophysiology of pulmonary arterial hypertension. Emerging therapies are aimed at these pathways. BMP9–based agonist therapies may represent a means to target the genetic and pathway defects in BMP signaling. Sotatercept targets upregulated activin signaling. Both approaches have the potential to generate disease–transforming therapies.